RECENT ECOLOGICAL SELECTION ON REGULATORY DIVERGENCE IS SHAPING CLINAL VARIATION IN SENECIO ON MOUNT ETNA. (21st June 2013) - Muir, Graham; Osborne, Owen G.; Sarasa, Jonas; Hiscock, Simon J.; Filatov, Dmitry A.
Abstract : The hybrid zone on Mount Etna (Sicily) between Senecio aethnensis and Senecio chrysanthemifolius (two morphologically and physiologically distinct species) is a classic example of an altitudinal cline. Hybridization at intermediate altitudes and gradients in phenotypic and life‐history traits occur along altitudinal transects of the volcano. The cline is considered to be a good example of ecological selection with species differences arising by divergent selection opposing gene flow. However, the possibility that the cline formed from recent secondary contact following an allopatric phase is difficult to exclude. We demonstrate a recent split between S. aethnensis and S. chrysanthemifolius (as recent as ∼32, 000 years ago) and sufficient gene flow (2 Nm > 1) to have prevented divergence (implicating a role for diversifying selection in the maintenance of the cline). Differentially expressed genes between S. aethnensis and S. chrysanthemifolius exhibit significantly higher genetic divergence relative to "expression invariant" controls, suggesting that species differences may in part be mediated by divergent selection on differentially expressed genes involved with altitude‐related adaptation. The recent split time and the absence of fixed differences between these two ecologically distinct species suggest the rapid evolution to an altitudinal cline involving selection on both sequence and expression variation.